Smart power meter - Goh, Poh Seng (Nanyang Technological University, 2023)
Today, electricity plays a major role in powering our daily lives mainly due to the world swiftly progressing thanks to modern technologies. Families' electricity expenditures are rising because of the increased production and use of gadgets, the majority of which need electricity to operate. Since customers can monitor their electricity usage to gain a better understanding of their habits and potentially lower their electricity costs, electricity marketers now advise families to switch to smart meters rather than standard ones. This project intends to construct a prototype smart meter. Aside from voltage and current, the prototype will also be able to track energy usage, power factor, active and reactive power, and total power. These parameters can be viewed via an application or web browser. The prototype consists of an energy sensor module Pzem-004t to receive the data, an ESP32 microcontroller with integrated wi-fi to read and transmit the data to the internet, which could then be monitored via Arduino cloud application or web dashboard. In addition to this, a liquid-crystal display (LCD) screen has also been included for users to see the readings directly. The prototype is built in an Acrylonitrile butadiene styrene (ABS) plastic as a form of enclosure. The testing results show that the smart meter can track the load’s electrical parameters and display these numbers on the LCD screen and Arduino dashboards.